Mechanism of lncRNA FOXD3-AS1/miR-338-3p in the malignant progression of nasopharyngeal carcinoma through ceRNA: LncRNA FOXD3-AS1/miR-338-3p in NPC progression - Li, Yuanming; Zhao, Shuai; Chen, Baiye (Cellular and Molecular Biology, 2023)
This work aimed to analyze the impact of lncRNA FOXD3-AS1 (F-A) on the regulation of miR-338-3p (M) on the proliferation (Pro), migration (Mig), and invasion (Inv) of nasopharyngeal carcinoma (NPC) cells. F-A and M levels in human normal nasopharyngeal (NNP) NP69 cells and NPC CNE1 and CNE2 cells were detected by real-time quantitative PCR. After transfection or cotransfection with F-A shRNA, miR-338-3p mimic (MM), and miR-338-3p inhibitor (MI), cell Pro, Mig, and Inv (PMI) were detected using CCK-8, scratch healing, and Transwell chamber experiments, respectively. As a result, relative to NP69 cells, F-A was upregulated in CNE1 and CNE2 cells, while M was downregulated (P<0.01). F-A in CNE1 and CNE2 cells was downregulated and M was upregulated relative to shF-A (P<0.01). Furthermore, shF-A and MM groups demonstrated drastically reduced cell proliferative activity, Mig, and Inv versus CNE1/CNE2 groups. The cell proliferative activity, Mig, and Inv number of the MI group increased substantially (P<0.01). The shF-A+MM group exhibited markedly reduced cell proliferative activity, Mig, and cell number of Inv relative to those of CNE1/CNE2 (P<0.01). Moreover, the shF-A+MI group exhibited greatly increased cell proliferative activity, Mig, and cell number of Inv versus the shF-A+MM group (P<0.01). In short, lncRNA F-A level was abnormally upregulated, and that of M was downregulated in NPC. Interfering with lncRNA F-A level can upregulate M expression. Silencing of lncRNA F-A can inhibit PMI of NPC cells.